1984
DOI: 10.1136/jcp.37.8.882
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of cross linked fibrin derivatives in plasma: an immunoassay using monoclonal antibodies.

Abstract: SUMMARY Fibrinogen degradation, fibrin polymerisation, and the insertion of cross links into fibrin by fibrin stabilising factor lead to the appearance of new antigenic determinants. Antibodies against these antigenic sites may react specifically with the derivatives but not with the parent molecules. We have utilised a monoclonal antibody, which interacts with the cross linked fragment D dimer and related high molecular weight fibrin derivatives, to develop an enzyme immunoassay which measures cross linked fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(59 citation statements)
references
References 13 publications
3
55
1
Order By: Relevance
“…However, the D-dimer levels of our study group agree reasonably well with the 75 ng/mL mean concentration documented by Whitaker et al in a study of 25 healthy blood donors (age unknown). 10 The present data also indicate that the increase in D-dimer concentration induced by peripheral IV insertion is relatively trivial compared with other non-thromboembolic etiologies. For example, Goldhaber et al reported the Ddimer concentration to be 2208 Ϯ 2236 ng/mL in 128 hospitalized patients with suspected pulmonary embolism but with normal pulmonary angiograms.…”
Section: Discussionsupporting
confidence: 59%
“…However, the D-dimer levels of our study group agree reasonably well with the 75 ng/mL mean concentration documented by Whitaker et al in a study of 25 healthy blood donors (age unknown). 10 The present data also indicate that the increase in D-dimer concentration induced by peripheral IV insertion is relatively trivial compared with other non-thromboembolic etiologies. For example, Goldhaber et al reported the Ddimer concentration to be 2208 Ϯ 2236 ng/mL in 128 hospitalized patients with suspected pulmonary embolism but with normal pulmonary angiograms.…”
Section: Discussionsupporting
confidence: 59%
“…D-dimer, a proteolytic derivative of degraded fibrin, can be detected in venous thromboembolism (VTE) as well as many other conditions, including inflammatory disorders, trauma, infections and neoplasia [13,14]. Although a positive D-dimer test has no significant diagnostic value, a negative D-dimer test has a high negative predictive value and makes the diagnosis of PE unlikely.…”
Section: D-dimermentioning
confidence: 99%
“…[4][5][6] The clinical conditions associated with elevated levels of D-dimer are numerous. Some of these include thrombosis (arterial or venous), pulmonary embolism, venous thrombosis, disseminated intravascular coagulation, myocardial infarction, stroke, postoperative state, liver disease, malignancy, and pregnancy.…”
mentioning
confidence: 99%